Consider the system of equations shown.

[tex]\[
\left\{\begin{array}{c}
y = x + 11 \\
-y = -x + 11
\end{array}\right.
\][/tex]

What is the solution to this system of equations?

A. [tex]\((0, 11)\)[/tex]

B. [tex]\((0, -11)\)[/tex]

C. no solution

D. infinitely many solutions



Answer :

To solve the system of equations, we need to determine whether there is a pair of [tex]\((x, y)\)[/tex] values that satisfies both equations simultaneously. Let's examine the system of equations step by step:

[tex]\[ \left\{\begin{array}{c} y = x + 11 \\ -y = -x + 11 \end{array}\right. \][/tex]

First, let's rewrite the second equation to make it easier to compare with the first equation:

[tex]\[ -y = -x + 11 \][/tex]

If we multiply both sides of this equation by [tex]\(-1\)[/tex] to get [tex]\(y\)[/tex] on one side, we obtain:

[tex]\[ y = x - 11 \][/tex]

Now, we have the following two equations:

1. [tex]\( y = x + 11 \)[/tex]
2. [tex]\( y = x - 11 \)[/tex]

Next, we equate the right-hand sides of these equations, since both expressions equal [tex]\( y \)[/tex]:

[tex]\[ x + 11 = x - 11 \][/tex]

Now, let's solve for [tex]\( x \)[/tex]:

[tex]\[ x + 11 = x - 11 \][/tex]

Subtract [tex]\( x \)[/tex] from both sides:

[tex]\[ 11 = -11 \][/tex]

This statement, [tex]\( 11 = -11 \)[/tex], is a contradiction. It is impossible for 11 to equal -11. Because we have reached a contradiction, it indicates that there is no pair [tex]\((x, y)\)[/tex] that satisfies both equations simultaneously.

Therefore, the system of equations has no solution.

Other Questions